Fruitful diversity in the territory of the Universidade Federal Rural of Pernambuco – UFRPE Sede (Research, Society and Development, 2022)
The Universidade Federal Rural de Pernambuco (UFRPE-Sede), located in the Dois Irmãos neighborhood in Recife/PE, has a wide fruitful, native and exotic diversity, due to the proximity of the Dois Irmãos State Park - Atlantic Forest Nature Conservation Unit of Pernambuco. This diversity contributes to the local population and is a source of research for the academic community at UFRPE. Because of this, the objective of the research is to score the botanical varieties with edible fruits present at UFRPE-Sede. The fruits identified during the survey: avocado (Persea americana), pineapple (Ananas comosus L. Merr), blackberry (Morus nigra L.), cattley guava (Psidium cattleianum Sabine), pond apple (Annona glabra L.), banana ( Musa X paradisiaca L.), caimito (Chrysophyllum cainito L.), hog-plum (Spondias mombin L.), cashew (Anacardium occidentale L.), coconut (Cocos nucifera L.), breadfruit (Artocarpus altilis), jamun (Syzygium cumini), jurubeba (Solanum stramoniifolium Jacq.), mango (Mangifera indica L.), papaya (Carica papaya L.), bitter melon (Momordica charantia L.) and surinam cherry (Eugenia uniflora L.). During the research, the social importance of these fruits was verified both for the academic community and for the research field in the different areas of knowledge at UFRPE.